Increasing Student Learning Participation in Natural Science Subjects Using Solar System Replicas Media Through Group Discussion Methods - Dwiastuti, Erfiyana (Universitas Sebelas Maret, 2022)
The purpose of this study was to increase student participation in class VI Mupel IPA using solar system replica media through group discussion methods. This research was conducted in 2 cycles. Student activity in cycle I with sufficient criteria increased with good criteria, namely from 56% learning outcomes, namely 10 of 18 students with an average value of 70, while in cycle II mastery increased to 100% or 18 of 18 students with an average value of 76 The conclusion of this study is that using replica media can increase the participation and learning outcomes of class VI students so that it has an impact on increasing abilities about time differences and their effects. The advice given is that a teacher should do a variety of learning using media so that it can improve the learning outcomes of class VI students at SDN 2 Nogosari.